Automating log analysis for industrial equipment maintenance using elastic stack - Nezhmetdinov Ramil; Kotyrova Shirin; Nezhmetdinova Ramilya; Kovalev Ilya (E3S Web of Conferences, 2023)
Contemporary technological equipment generates a substantial amount of data that can provide insights into system performance and help predict failures and critical errors. However, manual analysis of this data is time-consuming, and hence there is a need for automated tools to collect, process, and store log files. In this context, the study aims to develop an information system that can streamline log file analysis using ELK software solutions from the IT industry. The article explores the structure and components of ELK software and develops a software solution's structural diagram and architecture for practical use. Based on the conducted research, a software solution was implemented, and log data provided by the NASA Ames Research Center was analyzed and visualized through graphs and histograms. The study's novelty lies in using the ELK software stack for log file analysis of technological equipment, which is a widely used solution in the IT industry. The proposed system aims to reduce log file analysis time and help make informed decisions about system performance and maintenance.